LA IMPORTANCIA DEL DISEÑO DE ESTRATEGIAS CONGRUENTES CON EL CONTEXTO LOCAL PARA INCREMENTAR LA INSERCIÓN LABORAL DE JÓVENES: UN ANÁLISIS DEL IMPACTO DE REDES SOCIALES EN EL SURESTE DE MÉXICO - Linda Russell; Laura Garcia (European Scientific Journal, ESJ, 2015)
Each day world statistics on youth unemployment increase and there is an apparent lack of clear agreement on strategies to curb the current trends. The International Labour Organisation reported in 2013 that were more than 73 million unemployed youths between 15 and 24 years old. We argue in this paper that public policy is not always best adapted to local contexts when it comes to actions to raise workplace insertion amongst this segment of the population. With reference to a study of university graduates in a public university in the southeast of Mexico, we evaluate the impact of national public policy which takes pertinence and quality of higher education programmes as the key factors that influence school to work transition; but we also evaluate the impact of a well-known and highly used local factor which is ignored by the public policy models, namely horizontal social networks. Alternative strategies are proposed on the basis of the results of this study and we close by generalising the lessons learned in this study to the problems of youth unemployment in general.